Critical Walking Methodologies and Oblique Agitations of Place. (February 2022) - Springgay, Stephanie; Truman, Sarah E.
In this Editorial, we discuss WalkingLab 's approach to critical walking methodologies grounded in queer-feminist, anti-racist praxis, and argue for the need to critically account for understandings of place in times of ongoing crises. We then introduce the articles featured in this special issue. Authored by international scholars, each article in the special issue engages critically with walking methodologies and the concept place from oblique angles.